Five new Mallinella species from the Sundaland of Indonesia (Araneae, Zodariidae) - Dankittipakul, Pakawin; Jocqué, Rudy; Singtripop, Tippawan (Zootaxa, 2010)
Five new spider species belonging to the genus Mallinella Strand, 1906 (Araneae, Zodariidae) are described from the Greater Sunda (Sumatra, Borneo, Java) and adjacent smaller islands (Bali, Palau Belitung). These taxa are M. abdita sp. nov. (♂♀, East Kalimantan, Borneo), M. bifida sp. nov. (♂♀, East and South Kalimantan, Borneo), M. insulana sp. nov. (♂, Bali), and M. wiputrai sp. nov. (♂♀, Palau Belitung). Males that were considered by Simon to be conspecific with Storena melanognatha van Hasselt, 1882 prove to belong to an unknown species and here described as Mallinella simoni sp. nov. (♂, Java and Palau Belitung). New collections from Sundaland confirm that the first species is confined to Sumatra whereas M. simoni sp. nov. is hitherto known from Java and Palau Belitung. The known distribution of Mallinella albomaculata Bosmans & Hillyard, 1990, mentioned from Sulawesi, is here extended to the island of Borneo; the internal epigyne structure of this species is described and illustrated for the first time.